"Teenagers” Self Concept in Terms Of Gender, Cultural Background and Status at The Orphanage of Padang City "Teenagers” Self Concept in Terms of Gender, Cultural Background and Status at The Orphanage of Padang City - Syawaluddin Syawaluddin; Mega Iswari (Jurnal Konseling dan Pendidikan, 2014)
Self-concept of someone is heavily influenced by various factors, which include gender, cultural background and status. Related to guidance and counseling services in improving teenagers’ self-concept who live in an orphanage, is necessary to obtain a clear description about self- concept with a variety of factors that can affect it. This research uses a quantitative approach to type descriptive comparative. The research methods applied in the study was ex post facto with a sampling of data retrieval, research design using factorial design 2 x 4 x 2. Teenager’s self-concept of men and women are in middle category, average value of boys’ score are higher than girls, it means that  boys have  more positive view of themselves than girls. 2) Teenager’s self-concept in orphanages based on the cultural background of the Minangkabau, Mentawai, Java, and Batak are in middle category, there were no differences in teenager’ self-concept based on the cultural background of the Minangkabau, Mentawai, Java, and Batak who lives in an orphanage. 3) Teenager’s self-concept with orphan status and surrogate parents are in middle category, average value scores of teenager orphan status is higher than teenagers with the status of surrogate parents, it means that teenagers with orphan status have positive view of  himself rather than teenagers with surrogate parent status. 4) Teenager’s self-concept in terms of gender, cultural background, and status are in middle category, and there are interactions between gender variable, cultural background and status in explaining teenager’s self-concept. The implications of these results for the counselor are for a material consideration in the preparation of counseling service programs in improving teenager’s self-concept in an orphanage.